Phosphonium-based ionic liquids analogues and their physical properties - Kareem, Mukhtar A.; Mjalli, Farouq Sabri; Hashim, Mohd Ali; AlNashef, Inas M. (American Chemical Society, 2010)
New ionic liquids analogues, that is, deep eutectic solvents (DESs), have been successfully synthesized. These DESs have been synthesized by the reaction of phosphonium-based salts with different hydrogen bond donors. Many of these DESs have melting temperatures lower than 100 degrees C. Preliminary laboratory results showed that these DESs can be used in different applications, for example, electrochemical processes, separation of sugars, and so forth. Melting temperature, density, viscosity, pH, conductivity, and dissolved oxygen content of the novel phosphonium-based DESs were measured as a function of temperature. It was found that the type of the salt and hydrogen bond donor and the mole ratio of both compounds have a paramount effect on the studied properties.